Obstetric Intensive Care Admissions and Neonatal Outcomes - Rocha, Filipa Ramalho (2024)
Funding Information: This research was partially funded by the Hospital da Luz Lisboa under the initiative \u201CLuz Investiga\u00E7\u00E3o\u201D. The funding sources were not involved in the study design; collection, analysis and interpretation of data; the writing of the report; or the decision to submit the paper for publication. Publisher Copyright: © 2024 by the authors.